Apraxia for differentiating Alzheimer's disease from subcortical vascular dementia and mild cognitive impairment - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2013)
Although ideomotor limb apraxia is considered to be a typical sign of cortical pathologies such as Alzheimer's disease (AD), it has been also reported in subcortical neurodegenerative diseases and vascular lesions. We aimed to investigate the difference between AD, subcortical vascular dementia (SVaD) and mild cognitive impairment (MCI) patients by means of ideomotor limb apraxia frequency and severity. Ninety-six AD, 72 SVaD, and 84 MCI patients were assessed with the mini-mental status examination (MMSE), clinical dementia rating (CDR) and the apraxia screening test of TULIA (AST). Apraxia was significantly more frequent in the AD patients (32.3%) than in both of the SVaD (16.7%) and MCI (4.8%) patients. The frequency of apraxia was also significantly higher in SVaD patients than in MCI patients. AD patients had significantly lower apraxia scores than both SVaD and MCI patients. In addition, a significant difference was found between SVaD and MCI patients in terms of apraxia scores. These results suggest that the widespread belief of the association between apraxia and cortical dementias is not exactly correct. The significant difference between both of the dementia groups and the MCI patients suggests that the absence of apraxia can be an indicator for MCI diagnosis.
Keywords: apraxia; Alzheimer's disease; subcortical vascular dementia; mild cognitive impairment; IDEOMOTOR APRAXIA; HUNTINGTONS-DISEASE; LIMB APRAXIA; DIAGNOSIS; GESTURES; LESIONS; CORTEX; DAMAGE